KONSEP GLAM (GALERY,LIBRARY, ARCHIVE, DAN MUSEUM) SEBUAH KOLABORASI MEDIA INFORMASI DI MUHAMMADIYAH ABAD KE-2 - Muhamad Jubaidi (Publication Library and Information Science, 2021)
In Indonesia, the term Galery, Library, Archives and Museum (GLAM) is not well known. It's just that a similar collaboration model in the 1990s has emerged as a concept of innovation in the world of information service providers into libraries, archives and museums (LAM). The relationship between the roles between institutions that are similar in implementing their duties makes it unclear in the concept of development, as is the role of GLAM, which is to unify separate slices of information managed by each information source provider agency. The author tries to examine more deeply the concept of GLAM as an innovative collaborative media provider of information, especially in Muhammadiyah. This study aims to describe the concept of the Gallery, Library, Archives and Museum (GLAM) as a centre for information, data, documents and the organization's propagation media at Muhammadiyah. The author uses a qualitative method approach, as the author conducts observations, interviews, and literature reviews. The research found that at Muhammadiyah there had been an effort to collaborate the Gallery, Library, Archives and Museum (GLAM) as a complete information service center in the Muhammadiyah organization after the 1st Century Congress in 2010 in Yogyakarta.